Kadar Kalsium dan Karakteristik Fisik Tepung Cangkang Telur Unggas dengan Perendaman Berbagai Pelarut - Diode Yonata; Siti Aminah; Wikanastri Hersoelistyorini (Jurnal Pangan dan Gizi, 2017)
ABSTRACT The main component of poultry eggshell composition is CaCO3 which has potential to be a source of calcium. As food waste, poultry eggshells contain harmful components, organic compounds and the characteristic are rough, hard, flavorful fishy and have a les attractive color when used as food. The immercion process with chemical solution is known to improve the characteristics and purify the calcium level of eggshell flour. The general purpose of this research is to know the influence of solvent type on calcium level and physical characteristic of poultry eggshell flour. The method of research is experimental type using factorial completely randomized design, consist of 2 factors 16 treatments, namely type of solvent (HCl, CH3COOH, NaOH and H2O) and egshell species (chicken races, free-range chicken , duck and quail). Each treatment was repeated 3 times to obtain 48 units of experiments. Data on test results of calcium levels and physical characterstic analyzed using ANOVA statisticmethod followed by advanced test DMRT. The results shows a very real influence from the type of solvent and eggshell to the calcium level and physical characteristics of eggshell flour. Duck eggshell with CH3COOH soaking solution produce calcium level and physical characteristic of the best eggshell flour. Keywords: Eggshell, solvent, calcium, physical characteristic